Polimorfisasi dan Solvatomorfi Amoksisilina Trihidrat setelah Proses beku Kering - Nugrahani, Ilma; Asyarie, Sukmadjaja; Soewandhi, Sundani Nurono; Ibrahim, Slamet (UI Scholars Hub, 2010)
The polymorphismof amoxicillin has been identified after freeze drying process. The freeze dried amoxicillin have some specific physical properties different from their raw material, that was proved by DSC, XRD, and polarize microscope. Exothermal curve from DSC thermogram changes to endothermal curve, diffractogram XRD changes to different profile, and the crystal shows different habit. All of data showed that freeze drying process improve amoxicillin to different crystal form which has higher melting oxidation point and lower hydrate. The improvement of the crystal structure might be impact to change physical-pharmaceutical properties like dissolution, absorption, and change it antibiotic potency.